PENGARUH PEMBERIAN BOKASHI DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CAISIM (Brassica juncea L.) KULTIVAR TOSAKAN - Iman Sungkawa; Nurlyasari Nurlyasari (Agroswagati Jurnal Agronomi, 2017)
This research aims to know the influence of the interaction rate of bokashi and live spacing against growth and production of mustard plant (Brassica juncea L.) tosakan cultivars, to find out just know dose many of bokashi and live spacing which gives the best result in growth and production of mustard plant (Brassica juncea L.) tosakan cultivars, and than to find out the correlation between plant growth and yield components of mustard plant (Brassica juncea L.) tosakan cultivars.This research was carried out at the UPT BP3K Jalaksana, Kuningan district, in May until July 2013, arranged in the form randomized block design, factorial pattern, consisting of two factors, namely bokashi fertilizer and trunks. Dosing bokashi (B), which consists of 4 levels, namely : B0 = 0 bokashi tons/ha, B1 = 2 bokashi tons/ha, B2 = 4 bokashi tons/ha, and B3 = 6 bokashi tons/ha; Planting distance factor (J) which is made up of 3 levels, namely  : J1 = 40 cm x 30 cm, J2 = 40 cm x 40 cm, and J3 = 40 cm x 50 cm. Combination of as many as 12 treatment, with three replications, until there are 36 units of the experiment. Result of the research showed that there is a real interaction between the effects of the granting of bokashi and live spacing against the parameters of high-plant average at 21 HST, fresh weight per plant and fresh weigth per plot. Treatment of B2J2 (4 tonnes of bokashi/ha and planting distance of 40 cm x 40 cm) show the best influence on fresh weigth per plant that resulted in the production of 267,7 g/plant and fresh weight per plot that resulted in the productions of 3,3 kg/plot equivalent of 14,1 tons/ha. There is the real correlation between height growth components of plant age 14 and 21 HST, amount of leaf age 21 HST, and root volume, against fresh weigth per plot.